Effect of ultrasonic cleaning on the bond strength of fiber posts in oval canals filled with a premixed bioceramic root canal sealer - Fernando Peña Bengoa; Maria Consuelo Magasich Arze; Cristobal Macchiavello Noguera; Luiz Felipe Nunes Moreira; Augusto Shoji Kato; Carlos Eduardo Da Silveira Bueno (Restorative Dentistry & Endodontics, 2020)
ObjectiveThis study aimed to evaluate the effect of ultrasonic cleaning of the intracanal post space on the bond strength of fiber posts in oval canals filled with a premixed bioceramic (Bio-C Sealer [BIOC]) root canal sealer.Materials and MethodsFifty premolars were endodontically prepared and divided into 5 groups (n = 10), based on the type of root canal filling material used and the post space cleaning protocol. A1: gutta-percha + AH Plus (AHP) and post space preparation with ultrasonic cleaning, A2: gutta-percha + BIOC and post space preparation with ultrasonic cleaning, B1: gutta-percha + AHP and post space preparation, B2: gutta-percha + BIOC and post space preparation, C: control group. Fiber posts were cemented with a self-adhesive luting material, and 1 mm thick slices were sectioned from the middle and cervical third to evaluate the remaining filling material microscopically. The samples were subjected to a push-out test to analyze the bond strength of the fiber post, and the results were analyzed with the Shapiro-Wilk, Bonferroni, Kruskal-Wallis, and Mann-Whitney tests (p < 0.05). Failure modes were evaluated using optical microscopy.ResultsThe results showed that the fiber posts cemented in canals sealed with BIOC had lower bond strength than those sealed with AHP. The ultrasonic cleaning of the post space improved the bond strength of fiber posts in canals sealed with AHP, but not with BIOC.ConclusionsBIOC decreased the bond strength of fiber posts in oval canals, regardless of ultrasonic cleaning.